3, 3‐Bis(azidomethyl)oxetane (BAMO) Synthesis via Pentaerythritol Tosyl Derivates. Issue 9 (11th August 2017) - Maksimowski, Paweł; Kasztankiewicz, Anna B.; Kopacz, Wioleta
Abstract: 3, 3‐Bis(azidomethyl)oxetane (BAMO) is the most widely known azido oxetane in terms of the number of its polymers and copolymers applied as energetic binders e.g. in rocket propellants and plastic formulations of explosive materials. However, this compound continues to be a rather expensive monomer today. The aim of this study was to find a suitable synthetic route to produce this monomer in a large scale and to optimize it. The chosen route of synthesis was based on the application of tosyl pentaerythritol derivatives as the starting material. The BAMO synthesis by this method involves three stages, namely: pentaerythritol tosylation, tritosylpentaerythritol cyclization to 3, 3‐bis(tosylmethyl)oxetane (BTMO), and substitution of the BTMO tosyl groups with azido groups. In this work all the stages of the synthesis were optimized. BAMO was obtained in an overall yield of 61 %. The structure of the obtained compounds was verified by two techniques, namely: 1 HNMR and FT‐IR. Abstract :